Reduction of inappropriate exit prescriptions for proton pump inhibitors: A before‐after study using education paired with a web‐based quality‐improvement tool. Issue 5 (24th February 2015) - McDonald, Emily G.; Jones, Janelle; Green, Laurence; Jayaraman, Dev; Lee, Todd C.
Abstract : BACKGROUND: Proton pump inhibitors (PPIs) are overprescribed despite concerns regarding associated adverse drug events. OBJECTIVE: To reduce inappropriate PPI prescriptions using hospitalization as the point of contact to effect meaningful change. DESIGN: Before‐after study design. SETTING: Forty‐six–bed medical clinical teaching unit in a 417‐bed university teaching hospital in Montreal, Canada. PATIENTS: Four hundred sixty‐four consecutively admitted patients in the preintervention control group, and 640 consecutively admitted patients in the intervention group. INTERVENTION: A monthly educational intervention paired with a Web‐based quality improvement tool. MEASUREMENTS: We determined the proportion of patients admitted on PPIs, their indications, and appropriateness of use. We then compared the proportion of patients whose PPIs were discontinued at discharge before and after our intervention. RESULTS: Forty‐four percent of patients were already using a PPI prior to their hospitalization. In evaluated patients, only 54% of these patients had an evidence‐based indication for ongoing use. The proportion of PPIs discontinued at hospital discharge increased from 7.7% per month in the 6 months prior to intervention, to 18.5% per month postintervention ( P  = 0.03). CONCLUSIONS: Strategies to combat PPI overuse are needed to improve the overall quality of patient care. We significantly reduced discharge prescriptions for PPIs through the implementation of an educational initiative paired with a Web‐based quality improvement tool. An active interventional strategy is likely required considering the increasingly recognized and preventable adverse events associated with PPI misuse. Journal of Hospital Medicine 2015;10:281–286. © 2015 Society of Hospital Medicine